Analisis Pemanfaatan Media Online pada Pembelajaran Daring Fisika terhadap Motivasi Belajar Siswa - Fitria, Eka (Journal of Innovation in Teaching and Instructional Media, 2021)
The benefits of online media in physics online learning were investigated using the library research approach. In order to increase student learning motivation, Google Classroom and Zoom Meet were used as learning medium. The usage of Google Classroom and Zoom Meet as learning media effects improving student motivation at SMA Patra Mandiri 01 Palembang, according to research published in relevant journals and articles. In this context, the teaching and learning process can assist students understand the subject matter by generating desire, attractiveness, and motivation, as well as stimulating teaching and learning activities. The teacher's usage of learning media will motivate the students. If the learning media used is engaging, the material will be easier to comprehend, resulting in a more effective and efficient learning process.